Utility of Serology in Determining Helicobacter pylori Eradication after Therapy - Carlo A Fallone; Vivian G Loo; Alan N Barkun (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine the usefulness of four serological tests in confirming cure of H pylori infection before the previously reported six-month post-treatment delay.